Organic Waste as Fertilizer to Increase the Number of Peanuts (Arachis hypogaea L.) Flowers - Sobari, Enceng; Fathurohman, Ferdi (Jurnal Biodjati, 2021)
Peanut has high economic value and a significant role in food needs. the national food supply needs for peanuts to date have not been sufficient. This study aimed to determine the effect of organic waste which in this case is mushroom baglog compost and sheep manure on the flowers and pods of peanuts. The study was conducted on March-July 2018 in Subang district using the simple experimental plot method and group-randomized factorial design with two factors with each treatment done triplicate. The first factor is the baglog compost (soil without baglog compost, 90 g/plants, 120 gr/plants); the second factor is sheep manure dose (without sheep fertilizer, 90 gr/ plants, 120 gr/plants). The results showed that the application of baglog compost and sheep manure fertilizer at concentrations of 90 g and 120 g, respectively increased the number of flowers and potential pods. Moreover, Sheep manure fertilizer at a concentration of Â 120 g/plant, increased the dry weight of pods, seed, and 100 seeds even though was not significant.